A Bilateral Traumatic Hip Obturator Dislocation. (8th February 2016) - Karaarslan, Ahmet Adnan; Acar, Nihat; Karci, Tolga; Sesli, Erhan
Abstract : A case of a bilateral simultaneous traumatic obturator dislocation of both hip joints in an 18-year-old young man following a traffic accident is presented. We reduced the dislocated femoral heads immediately under general anesthesia followed by passive and active exercises and early full-weight bearing mobilization. After 5 years, the result was excellent.